Результати проведення конкурсу “Solar Decathlon KNUCA – 2013” - Четверіков, Ю. В. (Ways to Improve Construction Efficiency, 2013)
In this article is analyzed the experience of organizing in KNUCA an international competition “Solar Decathlon” relying on rules of world competition “Solar Decathlon”.